An Europium (III) Luminophore with Pressure‐Sensing Units: Effective Back Energy Transfer in Coordination Polymers with Hexadentate Porous Stable Networks. Issue 9 (2nd September 2020) - Hasegawa, Yasuchika; Sawanobori, Takuya; Kitagawa, Yuichi; Shoji, Sunao; Fushimi, Koji; Nakasaka, Yuta; Masuda, Takao; Hisaki, Ichiro
Abstract: A luminescent Eu III coordination polymer with O2 ‐sensing units under air, Eu III ‐hcpt (hcpt: 2, 3, 6, 7, 10, 11‐hexakis(4‐carboxy‐phenyl)triphenylene), is reported. The hexadentate carboxylic acids in hcpt ligands play an important role in the formation of tight‐packed three‐dimensional networks in Eu III ‐hcpt, giving hyper thermo‐stable structures (decomposition temperature=420 °C). The three‐dimensional porous network promotes bright luminescence (4f–4f emission quantum yield=70 %). The emission lifetime of Eu III ‐hcpt under vacuum (0.86 ms) was twice as large as that under O2 (0.48 ms, 1 atom:101.3 kPa). The Arrhenius analysis of the emission decay profile indicates that the back energy transfer (BEnT) from the emitting level of the europium(III) ion to the excited T1 state of the hcpt ligand should be activated at room temperature. The gradual decrease of emission lifetime is caused by the BEnT process in Eu III ‐hcpt. Finally, an advanced pressure‐sensitive luminophore is demonstrated. Abstract : Oxygen‐sensitive Eu III coordination polymers with strong luminescence properties under air were successfully fabricated by introducing hexadentate tight and porous three‐dimensional networks. The O2 ‐sensing property is based on the back energy transfer with activation energy. The O2 ‐sensitive coordination polymers have potential application in aerodynamic experiments.